2019
DOI: 10.1093/mnras/stz2948
|View full text |Cite
|
Sign up to set email alerts
|

Orbital dynamics of circumbinary planets

Abstract: We investigate the dynamics of a nonzero mass, circular orbit planet around an eccentric orbit binary for various values of the binary eccentricity, binary mass fraction, planet mass, and planet semi-major axis by means of numerical simulations. Previous studies investigated the secular dynamics mainly by approximate analytic methods. In the stationary inclination state, the planet and binary precess together with no change in relative tilt. For both prograde and retrograde planetary orbits, we explore the con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 46 publications
4
65
1
Order By: Relevance
“…For a misaligned non-zero mass planet orbiting around an eccentric binary, the critical inclination for the planet to librate depends on the binary eccentricity and the angular momentum ratio of the planet to the binary. The angle of the stationary inclination, or polar alignment, occurs at less than 90 • if the planet is massive (Farago & Laskar 2010;Zanazzi & Lai 2018;Chen et al 2019;. Furthermore, in Chen et al (2019) we found that the angular momentum transfer between the binary and a massive planet can be significant and the binary eccentricity can oscillate during the nodal libration.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…For a misaligned non-zero mass planet orbiting around an eccentric binary, the critical inclination for the planet to librate depends on the binary eccentricity and the angular momentum ratio of the planet to the binary. The angle of the stationary inclination, or polar alignment, occurs at less than 90 • if the planet is massive (Farago & Laskar 2010;Zanazzi & Lai 2018;Chen et al 2019;. Furthermore, in Chen et al (2019) we found that the angular momentum transfer between the binary and a massive planet can be significant and the binary eccentricity can oscillate during the nodal libration.…”
Section: Introductionmentioning
confidence: 73%
“…The angle of the stationary inclination, or polar alignment, occurs at less than 90 • if the planet is massive (Farago & Laskar 2010;Zanazzi & Lai 2018;Chen et al 2019;. Furthermore, in Chen et al (2019) we found that the angular momentum transfer between the binary and a massive planet can be significant and the binary eccentricity can oscillate during the nodal libration. The numerical simulation results are consistent with the analytic model in .…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…It is important to remark that outside the separatrix region, Ω circulates (prograde or retrograde direction). We recall that librating orbits and stationary angles change when brown dwarf companions are considered (Chen et al 2019), that is, for masses that are not compatible with CB detected planets. We explored the MMR location and widths around a wide variety of circumbinary inclined orbits for different binary mass ratios q = {0.2, 0.5, 1}.…”
Section: Inclined Circumbinary Planetsmentioning
confidence: 99%